A comprehensive comparative study on methylene blue removal from aqueous solution using biochars produced from rapeseed, whitewood, and seaweed via different thermal conversion technologies. (15th December 2022) - Güleç, Fatih; Williams, Orla; Kostas, Emily T.; Samson, Abby; Stevens, Lee A.; Lester, Edward
Highlights: Production of biochars from three distinct UK-based biomasses via three different thermal conversion technologies. Application of biochars in methylene blue removal from wastewater. Seaweed-based biochars exhibited the greatest potential in MB adsorption. Pseudo-second-order kinetic model explains the MB adsorption over seaweed-based biochars. The adsorption process was described well by the Langmuir isotherms for seaweed-based biochars. Abstract: This paper presents, for the first time, a comprehensive comparative analysis of the potential of using biochars from three distinctly different UK-sourced biomass feedstocks, produced via three different thermal processing techniques, to adsorb methylene blue dye. Biochars were made from rapeseed, whitewood, and seaweed ( Laminaria Digitata ), produced via hydrothermal conversion, pyrolysis, and torrefaction. Adsorption kinetic models were developed for each biochar at different temperatures, pH and initial dye concentrations. Relatively high levels of methylene blue adsorption capacity were achieved by seaweed-based biochars (∼150 mg/g), with reasonable levels for rapeseed-based biochars (∼60 mg/g), whilst adsorption levels were found to be relatively low for whitewood-based biochars (<30 mg/g). A Pseudo-second-order kinetic model provided the best fit with experimental results. The Langmuir adsorption isotherm showed a better fit for seaweed biochars, while the Freundlich adsorption isotherm was a better fit for the rapeseed-based biochars. The Langmuir adsorption isotherms showed relatively high maximum adsorption capacity (Q o ) for seaweed-based biochars; ∼175 mg/g for seaweed-Torrefaction and ∼ 117 mg/g for seaweed-Pyrolysis. Negative Gibbs free energy (ΔG°) values were observed for the seaweed-Torrefaction < seaweed-Pyrolysis < 0, which indicates that the methylene blue removal could be a thermodynamically favourable process due to the spontaneous nature of the adsorption. Our investigation has shown that the removal of methylene blue from wastewater could be a potential application for seaweed-based biochars as part of a holistic whole life cycle valorisation pathway. However, it is not suitable for all types of biomasses which emphasises the need for tailoring unique valorisation pathways for different types of biomasses.